2020
DOI: 10.1186/s12905-020-01062-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing women’s sex work in a Lebanese sample: results of a case-control study

Abstract: Background: Many constituents contribute to the rise of sex work in Lebanon such as the socioeconomic situation in the country (poverty, increased unemployment rates, and religious divisions), as well as the political and social instability. Several emotional and psychological factors such as depression, stress, anxiety, low self-esteem, emotional abuse, may force some people to rely on trading sex as a coping strategy for persevering. Therefore, it was deemed interesting to explore and understand factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Study findings also indicate that low financial self-efficacy was associated with HIV infection among women. The findings are supported by other studies which have documented poverty as one of the primary drivers for women to engage in sex work [ 13 , 26 , 53 55 ]. Women with low financial self-efficacy have less negotiating power with clients regarding safer sex, which puts them at high risk of HIV [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…Study findings also indicate that low financial self-efficacy was associated with HIV infection among women. The findings are supported by other studies which have documented poverty as one of the primary drivers for women to engage in sex work [ 13 , 26 , 53 55 ]. Women with low financial self-efficacy have less negotiating power with clients regarding safer sex, which puts them at high risk of HIV [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…Globally (2019), female sex workers have been identified among the population at the highest risk of contracting and spreading the HIV virus [5][6][7]. Additionally, studies conducted by Shava and others on HIV, confirmed the high incidence and prevalence of the disease among FSW [7][8][9][10][11][12][13][14][15][16][17]. In 2020, key populations (sex workers, gay men, men who have sex with men, transgender people, people who inject drugs, and people in prisons and others) and their sexual partners accounted for 65% of global new HIV infections, of which 8% were sex workers [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…There are different predictors of HIV prevalence which depend on country and context. Some of these predictors include inconsistent condom use (people who do not use condoms always) and having multiple sexual partners [12][13][14]. According to Fauk et al, personal (lack of knowledge of HIV testing and HIV and AIDS service and lack of knowledge of the existence of HIV infection), social (fear of stigma and discrimination), and healthcare provision (lack of trust, fear of disclosure of their HIV status by health professionals and limited availability of medications) barriers associated with HIV testing among male clients contribute to the high prevalence of HIV among FSW [17].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of mental disorders in FSW has been reported to be approximately 63.2%, including mood disorder (41.5%), anxiety (34.2%), and post-traumatic stress disorder (21.2%) [1][2][3]. Anxiety disorder is one of the most common mental health problems found in FSW [4]. This is based on many psychodynamic's risk factors among ex-FSW.…”
Section: Introductionmentioning
confidence: 99%